GFAP-Negative Subcutaneous Sacrococcygeal Extraspinal Ependymoma - Kazuya Goto; Hiroko Fujii; Gen Honjo; Satoshi Kore-eda (Karger Publishers, 2021)
Ependymomas are slowly growing glial tumors derived from the ependymal cells and usually occur in the central nervous system (CNS). Ependymomas rarely occur outside of the CNS and they are called extraspinal ependymomas. In spite of their metastatic potential, extraspinal ependymomas can be misdiagnosed for other benign mass like pilonidal cysts. The diagnosis is confirmed by histopathology and most of the cases are known to show glial fibrillary acidic protein (GFAP), S-100 protein, and keratin (AE1AE3) immunoreactivity. Herein, we present a case of GFAP-negative ependymoma, which presented as asymptomatic subcutaneous tumor of the left buttock and was clinically misdiagnosed as epidermal cyst. Our case indicates that ependymomas cannot be ruled out by lack of GFAP immunoreactivity and an asymptomatic subcutaneous mass could be a malignant tumor like ependymomas, which requires careful examinations.